MANAGEMENT OF THE IMPLEMENTATION OF TGT AND MAKE A MATCH TO IMPROVE PAI LEARNING OUTCOMES AND ETHICS AT SDN 19 LIMBORO MAJENE - Nurbahiya; Saprin; Usman (Tadbir: Jurnal Manajemen Pendidikan Islam, 2026)
Conventional learning methods often lead to low cognitive achievement in Islamic Education and Character (PAI-BP) among primary students, particularly through passive, teacher-centred approaches. To address this, the study investigates the comparative effectiveness of two cooperative learning models—Teams Games Tournament (TGT) and Make a Match in enhancing PAI-BP learning outcomes among Grade V students at SDN 19 Limboro. Using a True Experimental Design with a posttest-only control group, the research involved all 36 Grade V students, who were divided into two equivalent experimental groups via census sampling. Data were collected via a validated and reliable multiple-choice posttest. Prerequisite tests confirmed data normality and homogeneity, enabling the use of the Paired Sample t-test and the Independent Sample t-test for analysis. Results showed both models significantly improved learning outcomes (p < 0.001). However, TGT outperformed Make a Match, with mean posttest scores of 84.44 versus 80.00 (t = 2.224, p = 0.033). This confirms TGT’s superior effectiveness, likely due to its structured team competition and repeated review mechanism, which better support cognitive retention and motivation in PAI-BP. The study theoretically enriches Cooperative Learning Theory in non-exact, value-based subjects and offers practical, evidence-based guidance for educators to adopt TGT in religious education contexts.